2018
DOI: 10.29252/ijn.31.115.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer-assisted Education on the Knowledge and Performance of Nursing Students in Basic Cardiopulmonary Resuscitation

Abstract: Background & Aims: Cardiac arrest outside of a hospital is a major public health concern. Cardiopulmonary resuscitation (CPR) is an effort to protect the vital body organs (e.g., heart and lungs), which is performed based on a specific protocol. A proper CPR process depends on the acquisition of the required knowledge and skills by the resuscitator. The present study aimed to assess the effects of peer education based on the jigsaw puzzle method on the knowledge and performance of nursing students regarding ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, the PSKRE mean scores 2 months after the intervention were still higher in the two intervention groups than the control group, but the drop in the mean scores from the posttest to the follow-up was similar in the four study groups. Javaheri et al (2018) in their study of the effect of peer education and Graham et al (2019) and Gu et al (2020) by examining the impact of the FC further confirmed that the levels of knowledge at the follow-up were higher in the intervention group, a finding which is in line with the present study [ 3 , 38 , 39 ]. These studies had not measured the changes in the mean scores from the posttest to the follow-up, which could indicate a decrease in knowledge over time as a better criterion for assessing retention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the PSKRE mean scores 2 months after the intervention were still higher in the two intervention groups than the control group, but the drop in the mean scores from the posttest to the follow-up was similar in the four study groups. Javaheri et al (2018) in their study of the effect of peer education and Graham et al (2019) and Gu et al (2020) by examining the impact of the FC further confirmed that the levels of knowledge at the follow-up were higher in the intervention group, a finding which is in line with the present study [ 3 , 38 , 39 ]. These studies had not measured the changes in the mean scores from the posttest to the follow-up, which could indicate a decrease in knowledge over time as a better criterion for assessing retention.…”
Section: Discussionsupporting
confidence: 89%
“…In general, based on the study results, the integration of the two new methods of teaching could make the education of PS topics more effective than the conventional methods. The FC is also technology-dependent, and students plan for their learning based on their different learning abilities and styles [ 38 , 39 ]. This feature, along with the more attractiveness of the method, the bolder role of students in learning, as well as the less stress because of the NPE can be among the reasons for the greater impact of the integrated method of the FC and the NPE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peer education (based on peer evaluation) has been introduced as an effective training method to increase the quality of nursing reporting process[ 20 ] and holding continuous peer teaching courses could help maintain the knowledge and skills of health care providers. [ 14 ] Inconsistent results has been reported by Amini et al . [ 24 ] (2018).…”
Section: Discussionmentioning
confidence: 88%
“…[ 13 ] Teaching is a way to improve the current situation and is done in different ways such as peer teaching. In this way, peers work together to maximize the education level for each other and transfer their knowledge to each other,[ 14 ] and create a simple and safe learning environment according to the members' similar characteristics who share their experiences about it. [ 15 ] Peers have unique opportunities to affect the group[ 16 ] and can better share their knowledge and experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation